MERINO SHEEP BREEDING IN KYRGYZSTAN (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The current situation with sheepbreeding in the Kyrgyz Republic requires a creationof new system of work with manufacturers of raw stuff from sheep and establishment of marketingways for obtaining extra funds. A structure of enterprises and interchange of procedures for raisingprofitability of merino sheep breeding.
Keywords: sheep breeding, the Kyrgyz fine-wooled breed, livestock population, the Kyrgyz mountain merino, wool processing.